Diseño de la estructura metálica en prótesis parcial removible en el laboratorio dental - Ruiz López, Erick Alejandro (2025)
The designs of Cr Co removable partial dentures are very scarce, and they are not properly presented to dental technicians. The designs of these metal frameworks are necessary for the shaping of preliminary ideas of oral rehabilitations. These designs will accurately follow the course of the restoration, which will minimize the number of possible errors at the time of fabrication. Objective: To create a simplified design of Removable Partial Prosthesis for metallic structures of Chromium - Cobalt, through the systematization of professional experiences and knowledge of updated bibliography, to apply the technique in the dental laboratory. Materials and methods: A qualitative approach was adopted for the following report, with the objective of developing a simplified design of a Removable Partial Prosthesis for Chromium-Cobalt metal frameworks. The preparation process was based on the systematization of professional experiences and the search for updated bibliography, with the purpose of applying it within the laboratories. The report details the stages of the practical process elaborated, meticulously describing the procedures, methods and materials used, which reflects the learning acquired throughout this project. Results: A simplified protocol for the design of Chromium-Cobalt (Cr-Co) Removable Partial Prostheses (RP) was developed, in addition to incorporating key elements that facilitate the creation of future designs in this area. In order to design metal frameworks and achieve standardize and synthesize a general fabrication method to be able to be applied within the area of work and study. Conclusions: A standardized protocol was designed and established for the planning and fabrication of Removable Partial Prostheses with Cr - Co metallic structures. This procedure proposes in a methodical way the elaboration stages of the structural design, incorporating vital aspects for the generation of future designs, turning the design into an understandable and practical way of making them.